Метафорична, алегорична й символічна інтерпретація тексту: до питання універсальних методологій - Моклиця, Марія; Moklytsia, Maria (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті йдеться про необхідність актуалізації й розрізнення трьох потужних дискурсів культури - метафоричного, алегоричного й символічного -важливих у процесі аналізу та інтерпретації літературних текстів. Ці дискурси сформувалися в надрах середньовічної герменевтики на основі інтерпретаційних моделей грецько-римської античності. Названі способи інтерпретації тексту - це методи питомо філологічні, вони не дозволяють літературознавцю втратити з поля зору специфіку свого об'єкта. І це, вочевидь, найбільш універсальні з відомих моделей аналізу й інтерпретації вербальної сфери культури, бо підтвердили свою дієздатність у процесі апробації протягом тисячоліть. The article refers to the need to update and distinguish three powerful cultural discourses -metaphorical, allegorical and symbolic - in the process of analysis and interpretation of literary texts. These discourses were formed in the depths of medieval hermeneutics iterpretatsionnyh models based on the Greco-Roman antiquity. The allegorical interpretation of the text is inevitable when we are looking for meanings that have arisen in a rational way; symbolic interpretation is needed when searching for meanings that have arisen in the process of intuitive and emotional creativity; metaphorical interpretation is inevitable in the perception of a metaphorical work, she believes in restoring the chain of associations, which led to a paradoxical likening. These methods of interpretation of the text - is traditionally philological methods, they do not allow a literary critic lose sight of the specificity of its object. This is the most versatile of all known models of interpretation of the verbal sphere of culture, as confirmed its efficiency in the process of testing for millennia.
The Metaphorical, Allegorical and Symbolic Method of Interpretation of a Literary Text: the Question of Universal Methodologies
Keywords: метафора; алегорія; metaphor; allegory